Lymphomatous superficial lymph nodes: limitations of physical examination for accurate staging and response assessment - PG Gobbi; C Broglia; G Carnevale Maffe; A Ruga; E Molinari; E Ascari (Haematologica, 2002)
BACKGROUND AND OBJECTIVES: Superficial lymph nodes in lymphoma management are usually evaluated by physical examination. However the accuracy of this assessment has not been thoroughly tested and so it remains debated whether physical examination can meet the international requirements for clinical evaluation and response assessment. DESIGN AND METHODS: Palpatory size estimates of lymph nodes in 97 lymphoma patients were separately compared with ultrasonographic (US) measurements in cervical, supraclavicular, axillary and inguinal regions. Comparisons were made between the products of lymph node cross-sectional diameters, whose changes are critical to assess response. Statistical analysis was carried out by simple linear regression, in which the palpatory estimate was entered as the mean of the measurements separately taken by two different clinicians and the dependent variable was the US measurement. RESULTS: Physical examination tended to underestimate the lymph node size in all regions but appeared to be closely related to US measurements. However, while R2 was very high for cervical and inguinal lymph nodes (0.902 and 0.802, respectively), it was disappointingly low for lymph nodes in supraclavicular and axillary regions (0.529 and 0.368, respectively). INTERPRETATION AND CONCLUSIONS: This indicates that, with the current response criteria, pre- and post-treatment evaluation of cervical and inguinal lymph nodes makes substantial errors in 20-30% of cases when left to physical examination alone. Errors are even more numerous in supraclavicular and axillary regions. Thus, physical evaluation of superficial lymph nodes should be integrated by US or other imaging techniques for accurate fulfilment of the current standardized guidelines for response assessment.